Vitamin B12 and hepatitis C: Molecular biology and human pathology - Lott, William B. (The National Academy of Sciences, 2001)
Cobalamins are stored in high concentrations in the human liver and thus are available to participate in the regulation of hepatotropic virus functions. We show that cyanocobalamin (vitamin B12) inhibited the HCV internal ribosome entry site (IRES)-dependent translation of a reporter gene in vitro in a dose-dependent manner without significantly affecting the cap-dependent mechanism. Vitamin B12 failed to inhibit translation by IRES elements from encephalomyocarditis virus (EMCV) or classical swine fever virus (CSFV). We also demonstrate a relationship between the total cobalamin concentration in human sera and HCV viral load (a measure of viral replication in the host). The mean viral load was two orders of magnitude greater when the serum cobalamin concentration was above 200 pM (P < 0.003), suggesting that the total cobalamin concentration in an HCV-infected liver is biologically significant in HCV replication.